Efficacy Study of Mifepristone in Pre-induction Cervical Ripening and Induction of Labour (Nepal Medical College Journal, 2021)
This study was carried out to see the safety and efficacy of mifepristine as pre-induction cervical ripening agent along with misoprostol in induction of labour. It was a study done from January to June 2020 in Department of Obstetrics and Gynecology, Nepal Medical College Teaching Hospital. Total 120 patients were included in this study. Out of which, 60 women were be kept in test group who were induced by mifepristone and misoprostol and 60 women were kept in control group induced by misoprostol only. Patient characteristics, improvement of bishop score, maternal and neonatal outcome was recorded. Chi- square and T- Test were used to compare the result. Patient characteristics and the Bishop score at zero-hour of both the groups were similar. The mean bishop score 48 hours after use of mifepristine in test group was significantly increased in test group vs control group (P